Comparative computational modal analysis of uniform and tapered plates / N. A. Z. Abdullah and M. S. M. Sani - Abdullah, N. A. Z.; Sani, M. S. M. (Smart Manufacturing Research Institute (SMRI), 2024)
Thickness variation in structures has significant influence in their structural properties which makes it as an important consideration in engineering design. Varying thickness profile has gained many attention in its application due to the potential to optimise performance and reduce material usage. However, the impact of these thickness variations on modal behaviour of structures has not been fully understood. This study aims to investigate the effects of thickness variation on the modal properties of structural plates. Two plates with different configuration were modelled in MSC.Nastrab/Patran Software in which one plate has uniform thickness while the other has tapered thickness. Finite element modal analysis was performed to determine the natural frequencies and mode shapes of both plates. The results revealed that the plate with varying thickness has lower natural frequencies and its mode shapes are more complex and asymmetric compared to the plates with uniform thickness. These findings suggest that thickness variation can significantly alter the vibrational characteristics of structures which is important in design optimization of applications such as automotive and aerospace engineering.